2016
DOI: 10.6090/jarq.50.379
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Forest Structure and Biomass over Ten Years in a Lowland Amazonian Forest

Abstract: † These authors contributed equally to this work. AbstractThe topographic effects on biomass and its increment were evaluated for a terra-firme forest near Manaus, Brazil. We established three plots (60 × 60 m) on a plateau and at the bottom of a valley (namely baixio), and measured stem diameter at breast height D (> 10 cm) for tree and palm species in 2002 and 2012. Small trees (10 cm > D > 5 cm) were measured in subplots (20 × 60 m) within each plot. We also estimated tree height with the D -tree height H r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…These restrictive conditions in Maracá have been highlighted as a probable environmental limitation acting on the increase in height as a function of stem diameter when compared to less-restrictive environments (Ramírez-Narváez 2017). Differences in tree height between forest types along a topographic gradient were also found in central Amazonia (Suwa et al 2016). However, although mathematical distinctions in the H:D relation may exist at the microscale for specific species in the different forest types in the ecotone zone, there is no doubt that, at the level of the major forest formation, the growth trajectories are governed by common environmental fluctuations.…”
Section: Discussionmentioning
confidence: 95%
“…These restrictive conditions in Maracá have been highlighted as a probable environmental limitation acting on the increase in height as a function of stem diameter when compared to less-restrictive environments (Ramírez-Narváez 2017). Differences in tree height between forest types along a topographic gradient were also found in central Amazonia (Suwa et al 2016). However, although mathematical distinctions in the H:D relation may exist at the microscale for specific species in the different forest types in the ecotone zone, there is no doubt that, at the level of the major forest formation, the growth trajectories are governed by common environmental fluctuations.…”
Section: Discussionmentioning
confidence: 95%
“…2b). Suwa et al (2016) reported that the mortality of medium trees that are 40-50 cm dbh was higher than trees in the other size classes in the unlogged forest of ZF-2, in the central Amazon. The AGB increment due to the growth of surviving trees in the unlogged block Tab.…”
Section: Agb Stock In Unlogged Forest Blockmentioning
confidence: 99%